STRATEGI COPING SEBAGAI MEKANISME ADAPTIF MAHASISWA DALAM MENGATASI STRES AKADEMIK - Eka Dwi Ningsih; Surawan (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to explore and describe various coping strategies used by students in dealing with academic stress. Academic stress is a form of pressure that arises due to an imbalance between academic demands and students' ability to cope with them. This study uses a qualitative approach with a descriptive design, obtained through in-depth interviews with five students and documentation. The results of the study indicate that students face academic stress stemming from an accumulation of assignments, dual responsibilities, technical changes from lecturers, and the initial transition period of lectures. In dealing with this pressure, students apply two types of coping strategies, namely problem-focused coping and emotion-focused coping. Problem-focused strategies are carried out by prioritizing schedules and seeking social support. Meanwhile, emotion-focused coping involves engaging in spiritual activities, distancing oneself from stressors, and expressing emotions in a healthy manner. The conclusion of this study indicates that students tend to use a combination of coping strategies tailored to the type of stress they face. Effective coping strategies have been proven to help students manage stress adaptively, enabling them to continue performing well in both academic and non-academic activities